1975
DOI: 10.1099/00221287-89-2-319
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Phosphate and Volatile Fatty Acid Salts on the Growth of Rumen Bacteria

Abstract: Bacterial cultures in media with a low (0.38 %, w/v) initial glucose concentration showed much smaller pH changes during growth than cultures grown in media with excess (1.25 %, w/v) glucose. Increasing the concentration of the phosphate or volatile fatty acid salt (VFA salt, i.e. acetate, propionate or butyrate) in the media had no beneficial effect on cultures of Streptococcus bovis or Lactobacillus plantarum which had only minor falls in pH during growth (final pH 3 6.0), but increased the dry weight yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 9 publications
(8 reference statements)
1
8
0
1
Order By: Relevance
“…During biological reaction processes, the VFAs can accumulate to a high level and thus may be stimulatory, inhibitory or even toxic to fermentative bacteria, depending on their concentration [3][4][5][6][7]. The inhibition mechanism of VFAs on fermentative bacteria has been analyzed previously.…”
Section: Introductionmentioning
confidence: 99%
“…During biological reaction processes, the VFAs can accumulate to a high level and thus may be stimulatory, inhibitory or even toxic to fermentative bacteria, depending on their concentration [3][4][5][6][7]. The inhibition mechanism of VFAs on fermentative bacteria has been analyzed previously.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that maintaining the growth pH at 7.0 not only enabled complete substrate breakdown but also maintained a higher cell viability. Acetic acid is toxic to some micro-organisms (Hentges, 1967;Stewart, 1975) and it accumulates in anaerobic digesters operating under non-optimal conditions (McCarty, 1964). The inhibitory effect of volatile fatty acids is due to the undissociated form (Hentges, 1967;Meynell, 1963).…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…Hungate (1966) estime qu'elle est comprise entre 2 et 6 % de la matière sèche (MS) et Stewart (1975), pour des bactéries en culture pure, entre 2 et 2,8 %. Sur des prélèvements effectués in vivo, les valeurs se situent en général entre 1 et 2 % (Durand, non publié ;Martinez, 1972 ;Czerkawski, 1976 ;Van Nevel et Demeyer, 1977 …”
Section: Introductionunclassified